1981
DOI: 10.1007/bf00844272
|View full text |Cite
|
Sign up to set email alerts
|

Psychological correlates of the Type A behavior pattern

Abstract: Psychological characteristics of 384 adult males classified as Type A or Type B by the structured interview were examined. Subjects classified Type A differed significantly from subjects classified Type B on a number of psychological scales including measures of aggression, autonomy, extroversion, and impulsiveness but not on measures of psychological distress. The extent to which pencil and paper questionnaire assessments of Type A differ from structured interview ratings was also studied. Correlations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
3
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(76 citation statements)
references
References 31 publications
10
62
3
1
Order By: Relevance
“…The significant associations of the Type A scores with neuroticism, trait anxiety, trait tension, and hostility suggest Type A to be associated with sustained high levels of psychophysiological arousal. These conclusions are consistent with those of Irvine et al (1982) with regard to the JAS, and those of Chesney et al (1981) and Smith (1984) with regard to the FTAS. The present study also found a significant correlation between Type A (on both the JAS and FTAS) and psychoticism scores on the EPQ.…”
Section: Discussionsupporting
confidence: 93%
“…The significant associations of the Type A scores with neuroticism, trait anxiety, trait tension, and hostility suggest Type A to be associated with sustained high levels of psychophysiological arousal. These conclusions are consistent with those of Irvine et al (1982) with regard to the JAS, and those of Chesney et al (1981) and Smith (1984) with regard to the FTAS. The present study also found a significant correlation between Type A (on both the JAS and FTAS) and psychoticism scores on the EPQ.…”
Section: Discussionsupporting
confidence: 93%
“…Later studies however have found that the hostility/anger items of the Type A/B scales both differentiate between these personality types (Rosenman, Rahe, Borhani, & Feinleib, 1976;Chesney, Black, Chadwick, & Rosenman, 1981) Dembroski, Dimsdale and Hackett (1985) found that Global TABP (substantially correlated with explosiveness of speech, rapid-acce1erated speech and response latency) was completely unrelated to the severity of coronary artery disease. In this study, anger-in was the strongest predictor of CHD, and these results were consistent with an earlier study (Dembroski et al, 1985) in which potential for CHD was predictive only for those individuals who did notexpress their hostility openly.…”
Section: Cardiovascular Reactivitymentioning
confidence: 99%
“…May & Kline, 1987), the total score appears unrelated to extraversion (Furnham, 1984;Irvine etal., 1982;Langeluddecke & Tennant, 1986;May & Kline, 1987;Ray & Bozek, 1980). Since different measures of Type A have not always been found to be highly interrelated themselves (Chesney et al, 1981 ;Langeluddecke & Tennant, 1986;Mathews, Krantz, Dembroski & MacDougall, 1982), caution must be exercised when generalizing across measures. The Framingham Type A Scale used in the present study, or shorter versions of it, have been shown to be positively correlated with psychological distress and neuroticism (Chesney et al, 1981 ;Cramer, 1990;Haynes et al, 1978;Langeluddecke & Tennant, 1986;Smith, Houston & Zurawski, 1983 ;Smith & O'Keeffe, 1985) but unrelated to extraversion (Langeluddecke & Tennant, 1986).…”
mentioning
confidence: 99%